From Hypertension to Heart Failure: Role of Novel Beta Blocker - IA Arso (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
As one of the risk factors of cardiovascular diseases, particularly coronary heart disease and .....